Nigeria: index to Federal decrees in circulation: 1990 - 1998 - Okubule, Ayodeji O./Compiler (1999)
This index traces all Decrees by the Federal Government of Nigeria issued between 1990 and 1998.
It contains 492 titles of various Decrees issued by the Federal Government.
rua 30/08/16
Loans
Keywords: Indexes; Decrees; Nigeria